Circulant orbitals for atoms and molecules - Parr, Robert G. (1981)
Circulant orbitals ϕ(n) for a closed-shell system are the orbitals obtained when the N canonical orthonormal Hartree-Fock orbitals λ([unk]) are subjected to a unitary transformation which is the discrete Fourier transformation: ϕ(n) = 1/√N Σ([unk])λ([unk])ω((n-1)([unk]-1)), where ω = exp(2πi/N). Electron densities associated with the orbitals ϕ(n) are each close to the average total electron density. The Fock matrix, diagonal for canonical orbitals, for circulant orbitals is a Hermitian circulant matrix, ε(m, m+q) = 1/N Σ([unk])ε([unk])ω(q([unk]-1)), where the ε([unk]) are the canonical orbital energies. The states ^Fϕ(n) are uniformly distributed on the surface of a sphere in Hilbert space.